2017
DOI: 10.1155/2017/2121878
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitaceae Seed Protein Hydrolysates as a Potential Source of Bioactive Peptides with Functional Properties

Abstract: Seeds from Cucurbitaceae plants (squashes, pumpkins, melons, etc.) have been used both as protein-rich food ingredients and nutraceutical agents by many indigenous cultures for millennia. However, relatively little is known about the bioactive components (e.g., peptides) of the Cucurbitaceae seed proteins (CSP) and their specific effects on human health. Therefore, this paper aims to provide a comprehensive review of latest research on bioactive and functional properties of CSP isolates and hydrolysates. Enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 59 publications
4
20
0
Order By: Relevance
“…(2017) evaluated the antioxidant activity of flaxseed protein isolate and detected four peptides in the antioxidant protein fraction released with Alcalase® 37 . Several bioactive peptides (antifungal, antimicrobial, anticarcinogenic and ACE inhibitors) were obtained from seed proteins of Cucurbitaceae such as pumpkin, squash, and melon 7 . However, the peptides mentioned above differ from those identified in our study due to the use of a different combination of methods and enzymes.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…(2017) evaluated the antioxidant activity of flaxseed protein isolate and detected four peptides in the antioxidant protein fraction released with Alcalase® 37 . Several bioactive peptides (antifungal, antimicrobial, anticarcinogenic and ACE inhibitors) were obtained from seed proteins of Cucurbitaceae such as pumpkin, squash, and melon 7 . However, the peptides mentioned above differ from those identified in our study due to the use of a different combination of methods and enzymes.…”
Section: Resultsmentioning
confidence: 71%
“…Seeds, cakes, and vegetable oils are also rich in bioactive compounds (phytosterols, tocopherols, phenolic compounds, bioactive proteins, and peptides). Their positive effects on human health include lowering blood pressure, reducing blood cholesterol, regulating blood glucose levels, improving the functioning of the digestive and nervous systems, and regulating the endocrine system 6,7 . For example, nigella seeds have been found to contribute to the production of red blood cells, increasing the speed and effectiveness of anemia treatment, 8 and regular consumption of unrefined rapeseed oil may be used to treat depression 9 …”
Section: Introductionmentioning
confidence: 99%
“…Based on the data found in the literature [ 20 ], it can be concluded that these proteins were extracted and purified in a neutral or acidic environment. Moreover, according to Ozuna and León-Galván [ 5 ], the composition of protein preparations depends on the chemical composition and characteristics of the proteins contained in the raw material. In most cases, acetylation had no effect on the protein content.…”
Section: Resultsmentioning
confidence: 99%
“…In Europe, pumpkin ( Cucurbita pepo L.) is cultivated in the middle south region, primarily for oil production from seed, where the main by-product from oil extraction is defatted pumpkin cake, which contains up to 65% protein [ 2 , 3 ]. Due to the high protein content, this by-product left over from pumpkin oil seed extraction is considered by many authors as one of the most attractive and promising sources of vegetable proteins with proven health-promoting and functional effects [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation